Prediction of Jamar Grip Strength Value Using Modified Aneroid Spyhgmomanometer Cuff Method - Lusia Pujianita; Tertianto Prabowo; Marietta Shanti Prananta (International Journal of Integrated Health Sciences, 2017)
Objective: To examine the prediction of Jamar grip strength value by using aneroid sphygmomanometer cuff method in adults.Methods: This study involved 120 subjects, aged 20–59 years old. The grip strength of subjects were measured using Jamar dynamometer and aneroid sphygmomanometer cuff method. Spearman analysis was used to evaluate the correlation between variables and grip strength. Forward stepwise was used to analyze the regression of Jamar dynamometer using aneroid sphygmomanometer cuff method. Results: There was a weak correlation (r<0.4) between grip strength with age and BMI, moderate correlation (r = 0.4–0.6) for grip circumference, and also strong correlation r= (0.6–0.8) for sex, hand length, and hand width. Jamar grip strength value can be predicted using spyghmomanometer with the formula of (0.1157 x Sphygmomanometer grip strength value) – (5.696 x sex) + (0.0824 x age) (female =1, male= 0).Conclusions: Grip strength correlates with physiological variables. The variables to predict Jamar grip strength using sphygmomanometer are sex and age. Regression analysis shows that spyhgmomanometer can be used as an alternative to measure grip strength and has a valid value to predict the Jamar grip strength value. Keywords: Adult, grip strength, Jamar dynamometer, sphygmomanometer, prediction formula DOI: 10.15850/ijihs.v5n1.958